2011
DOI: 10.1080/00207233.2011.582724
|View full text |Cite
|
Sign up to set email alerts
|

Water scenarios in the Gaza Strip, Palestine: thirst, hunger and disease

Abstract: This paper examines the interacting problems which govern poor access to quality drinking water, as well as the related problems of solid waste treatment and recycling. The need for a stable political resolution of the Israel-Palestine conflict is paramount. Although long-term solutions to the crisis require a regional political solution, there are several local activities that can reduce the degradation of water supplies and larger eco-systems. These include desalination of seawater and brackish water, water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Numerous natural and anthropogenic factors contribute to making Gaza strip the worst-case scenario in term of water problems (Al-Agha, 1995;Shomar, 2006;Shomar, 2011b). A number of studies and research have reported high microbiological and chemical pollution levels of groundwater, mainly due to over-abstraction and improper disposal of wastewater (Qahman & Larabi, 2006;Shomar et al, 2006;Yassin et al, 2006;Shomar et al, 2010a;Shomar, 2011b;Abbas et al, 2013;Jabal et al, 2015). Nevertheless, the incidence of waterborne diseases among the population of Gaza strip has not been given sufficient attention by previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous natural and anthropogenic factors contribute to making Gaza strip the worst-case scenario in term of water problems (Al-Agha, 1995;Shomar, 2006;Shomar, 2011b). A number of studies and research have reported high microbiological and chemical pollution levels of groundwater, mainly due to over-abstraction and improper disposal of wastewater (Qahman & Larabi, 2006;Shomar et al, 2006;Yassin et al, 2006;Shomar et al, 2010a;Shomar, 2011b;Abbas et al, 2013;Jabal et al, 2015). Nevertheless, the incidence of waterborne diseases among the population of Gaza strip has not been given sufficient attention by previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…The difficulties of the Palestinian people have not gone unnoticed by the international community with many countries providing hundreds of millions of dollars in funding and support over recent decades (World Bank Group, 2018). There has also been extensive research undertaken to understand the infrastructure requirements for Palestine in water supply (Bohannon, 2006;Brooks and Trottier, 2010;EWASH, 2015;Haddad, 2009;Ludwig, 2016;McNeill et al, 2009;PWA, 2011PWA, , 2012PWA, , 2014Shadeed and Almasri, 2010;Shomar, 2011;Shomar et al, 2010;Weibel and Elmughanni, 2014;World Bank, 2009; in energy supply (Abu Hamed et al, 2012;De Meij et al, 2016;Evans, 2015;Henderson, 2014;Ibrik, 2009;Juaidi et al, 2016;MAS, 2014;UNISPAL, 2007;World Bank, 2014a; in wastewater management (Abusharbak, 2004;Dotan et al, 2016;Fatta et al, 2004;Nassar, 2015); in solid waste management (D-Waste, 2014;El Baba et al, 2015;Isaac et al, 2005;Sa'di); in transport (Garb, 1998;MoPWH, 2012;Suisman et al, 2005); and in digital communications (Paltrade, 2010;World Bank, 2016). Our analysis suggests these research efforts have been well prioritised in water and energy, with emphasis appropriately given to the acute crisis in the Gaza Strip.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, researchers and agencies have begun to look across multiple sectors to fill these gaps. However, due to their inherent complexities such analyses have been limited to just two sectors, such as water and wastewater (Afifi, 2006;Eting, 2015;Fatta et al, 2004;McNeill et al, 2009;PWA, 2012;Shomar, 2011), water and energy (PWA, 2015), and energy and waste (Ouda, 2013). Analyses looking at the water and energy nexus have also been conducted at a Middle East regional level to allow for resources to be shared and traded across borders (Gabriel et al, 2016;Siddiqi and Anadon, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Yet for this to become a reality, a stable peace with Israel, a stable Palestinian government, and the political will to adapt new technologies and governance structures for sustainable water and sanitation systems. Until then Gazans will continue to be deprived of this basic necessity essential to good health and high quality of life and to life itself [37]. Based on long term-research in the Middle East, Figure 3 summarizes the general framework of research on water issues.…”
Section: Water and Environment In Palestine: Past And Presentmentioning
confidence: 99%